Noise levels of dental equipment used in a dental school - Acuña Vesga, Andrea Patricia; Díaz Ramírez, Leidy Carine; Almario Barrera, Andrea Johanna; Peñuela Sánchez, Adriana Esperanza; Castellanos Domínguez, Yeny Zulay (Revista Cuidarte, 2022)
Introduction: Dental professionals are exposed to different noise levels in their work environment during their clinical practice, mainly caused by dental instruments and rotary instruments used on a daily basis. Noise levels may vary according to the type of clinical specialty. Objective: To determine noise levels during dental procedures in dental school clinics. Materials and Methods: An analytical cross-sectional study was conducted by means of non-probability convenience sampling to determine dental specialties to be evaluated. BENETECH GM1352 30-130dB Digital Sound Level Meter with accuracy +/- 1.5 dB and A weighting was used for measurements. Mann-Whitney U and Kruskal-Wallis H tests were used to identify differences in noise levels among dental specialties. Results: Measured median noise level was 75.94 dB (RCI 74.21 -77.51), dental surgery was identified to have the highest noise among clinical specialties (median 77.34 and RCI 76.44 -79.4 dB). Conclusions: Dental surgery, oral rehabilitation, endodontics and pediatric dentistry were found to be the clinical specialties where noise exposure is within the limits established by Colombian regulations for noise in the workplace. How to cite this article: Acuña-Vesga Andrea Patricia, Díaz-Ramírez Leidy Carine Almario- Barrera Andrea Johanna, Peñuela-Sánchez Adriana Esperanza, Castellanos-Domínguez Yeny Zulay. Niveles de ruido generados en procedimientos realizados en una facultad de odontología. Revista Cuidarte. 2022;13(1):e2251. http://dx.doi.org/10.15649/cuidarte.2251